Synthesis and Characterization of One-Dimensional Porous (Zn,Cd)S/SiO2 Composite Nanostructural Materials - Xiuli Fu; Guijun Ban; Dan Li; Hanyuan Chen; Zhijian Peng (Advances in Condensed Matter Physics)
One-dimensional (1D) porous (Zn,Cd)S/SiO2 composite nanostructural materials were synthesized by thermal evaporation of ZnS and CdS mixture powder at 950°C. The nanomaterials were collected from silicon wafers which were coated with 10 nm thick gold and were set apart from the source about 10 cm away. The diameter of the as-prepared 1D porous composite nanostructures is in the range of 1–1.5 μm and their lengths are up to tens to hundreds of micrometers. The photoluminescence spectra measured at different temperatures of the prepared nanostructures display a similar broadband signature, which can be fitted by Gaussian function into three emission peaks centered at 477, 536, and 588 nm and attributed to band edge emission, neutral oxygen vacancies, and antisymmetric stretching of Si–O–Si and nonstoichiometric SiOx (1<x<2), respectively.